2021
DOI: 10.1111/codi.15694
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of carcinoembryonic antigen combined with carbohydrate antigen 19‐9 following neoadjuvant chemoradiotherapy in patients with locally advanced rectal cancer

Abstract: Aim The clinical significance of carcinoembryonic antigen (CEA) combined with carbohydrate antigen 19‐9 (CA19‐9) in patients with rectal cancer is not well established. The aim of this study was to determine the prognostic value of these combined tumour markers in patients with locally advanced rectal cancer (LARC) treated with neoadjuvant chemoradiotherapy (nCRT). Method A total of 687 consecutive patients with LARC who underwent nCRT and radical surgery were analysed. Tumour characteristics, recurrence‐free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(44 reference statements)
2
7
0
Order By: Relevance
“…studies had indicated that various clinical factors could affect the pathological reaction of nCRT in patients with LARC, including the CEA and CA199 level, and clinical staging[26,27]. In our investigation, both univariate and multivariate logistic regression analyses showed that age (P < 0.01) and clinical stage (P < 0.01) could be an independent predictor of good response after nCRT in patients with LARC.…”
supporting
confidence: 47%
“…studies had indicated that various clinical factors could affect the pathological reaction of nCRT in patients with LARC, including the CEA and CA199 level, and clinical staging[26,27]. In our investigation, both univariate and multivariate logistic regression analyses showed that age (P < 0.01) and clinical stage (P < 0.01) could be an independent predictor of good response after nCRT in patients with LARC.…”
supporting
confidence: 47%
“…Previous studies had indicated that various clinical factors could affect the pathological reaction of nCRT in patients with LARC, including the CEA and CA199 level, and clinical staging [ 27 , 28 ]. In our investigation, both univariate and multivariate logistic regression analyses show that age ( P < 0.01) and clinical stage ( P < 0.01) can be as an independent predictor of good response after nCRT in patients with LARC.…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to metastasis to other organs or local recurrence, the long-term survival of LARC is unsatisfactory ( 4 , 17 ). To achieve a better prognosis, imaging ( 39 , 40 ), carcinoembryonic antigen (CEA) combined with carbohydrate antigen 19-9 (CA19-9) ( 41 ), platelet-associated biomarkers ( 42 ), and circulating tumor DNA (ctDNA) ( 43 ) must be dynamically estimated and promptly evaluated. A more personalized treatment regimen is preferable for high risk patients, and novel combination regimens should be further investigated.…”
Section: Discussionmentioning
confidence: 99%